Prevalence of Chronic Venous Diseases in Students of Ivano-Frankivsk National Medical University - Rostyslav Sabadosh; Mykola Riziuk; Nazarii Ryziuk (Galician Medical Journal, 2019)
The Objective of the Research was to increase the frequency of detecting chronic venous disorders in young people by surveing the students using a specially designed questionnaire with an analysis of its results for timely treatment.